Pendampingan Siswa SMA Muhammadiyah Ponorogo untuk Peningkatan Literasi Teks Berbahasa Inggris dalam Konteks Muhammadiyah - Elok Putri Nimasari; Rohfin Andria Gestanti; Restu Mufanti (Jurnal Pengabdian Pada Masyarakat, 2021)
MUHAMMADIYAH-CONTEXT ENGLISH LITERACY TEXT DEVELOPMENT FOR COMMUNITY SERVICES. This community service was conducted based on early-observation in SMA Muhammadiyah Ponorogo. This high school has implemented billingual curriculum for a year. However, students text literacy towards English texts were limited. Universitas Muhammadiyah Ponorogo has focused to develop community services in all field studies particularly those school under Muhammadiyah-management. In this community service report, the authors would like to report Muhammadiyah-based literacy text development for SMA Muhammadiyah Ponorogo’s case. Authors are expertise in education field especially in language test assessment and text literacy. The community service was conducted in even semester of year 2020. Although the situation did not allow authors to conduct training face-to-face due to coronavirus pandemic, the community service was still held through webinars. It aimed to train students improving their English-text literacy certainly in the context of Muhammadiyah. Three day webinars were conducted for community services consisted of introduction of bilingual curriculum and its relation to Muhammadiyah-based texts, and strategies to improve students’ literacy.